TRAINING RETURN-ON-INVESTMENT: SUATU PERSPEKTIF DALAM MENGEVALUASI KEEFEKTIFAN PROGRAM PELATIHAN - Oki Sunardi (Universitas Bunda Mulia, 2017)
Every year new challenges emerge in the field of training and development, for example, competency development, outsourcing, e-learning, and knowledge management. The purpose of this study is to conceptualize the different dimensions of access to employee development. The concept of Kirkpatrick’s Four-Level Framework can be used to choose which levels are appropriate in evaluating a training program. Lilly’s Four Steps of Computing ROI training can also be adapted to the ROI calculation process. The main issue, in the pursuit of profitability and competitive advantage, top management is looking at all functions for a return-on-investment. The main question is, “is it really the training program itself that affects the employee performance?” This research uses ‘time series with comparison group’ technique as a tool to isolate the effects of training. Once the isolation is completed, the ROI calculation can be analyzed then. Keywords: Effectiveness of training; isolating the effects of training; time series with comparison group; ROI calculation.